20-minute crafts - Hands On Crafts for Kids. (New York : Sterling Pub., 2001)
Presents 48 project ideas including lists of needed materials, full-size patterns, and color photographs of the completed projects.
"A Sterling/Chapelle book."
Includes index.
Keywords: Handicraft -- Juvenile literature; Handicraft